Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species - Martínez-Revelo, Diego Esteban; Lopera-Toro, Alejandro; Medina, Claudia A. (Zootaxa, 2020)
We present a review of Scatimus Erichson (Coleoptera: Scarabaeidae: Scarabaeinae: Ateuchini: Scatimina) in Colombia, with the description of S. strenua new species from the Central Andes (Antioquia Department). Records of S. strandi Balthasar from southwestern Colombia (Caquetá and Nariño Departments) are validated. The distributions of S. ovatus Harold from the Magdalena, Chocó-Darién, and Sierra Nevada de Santa Marta provinces and S. fernandezi Martínez in the eastern foothills of the Eastern Cordillera (Orinoco-Amazon) are confirmed. New departmental records and distribution maps for Colombia are presented; an updated key for the taxonomic identification of Scatimus is included. With a total of four species, Colombia has the second highest Scatimus species richness of any country.